Four-item itch questionnaire – validation of questionnaire - Reich, Adam; Mędrek, Karolina; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . A competent measurement of itch still remains a challenge. Objective . To develop and validate the Polish itch questionnaire. Material and methods . A total of 279 patients (144 women and 135 men) aged between 16 and 89 years suffering from chronic pruritic dermatoses were included in the study. The pruritus severity was assessed according to the itch questionnaire as well as the visual analogue scale. In addition, quality of life, level of depressive symptoms and the degree of emotional stress experienced prior to the disease outbreak were evaluated. The test-retest comparison was performed in 41 patients by double completion of the itch questionnaire. Results . The developed questionnaire showed good convergent discriminant validity. Based on the achieved results significant differences could be detected between itch in atopic dermatitis (13.7 ±4.4 scores) and itch in patients with psoriasis (9.4 ±4.7 scores, p < 0.001). The itch questionnaire also showed acceptable internal consistency (Cronbach α = 0.64), and responses to single questions significantly correlated with total itch scoring. The results achieved with the itch questionnaire were also reproducible (ICC = 0.7). Conclusions . The described itch questionnaire may be used both in scientific trials and in routine daily practice.